2012
DOI: 10.1002/qua.24063
|View full text |Cite
|
Sign up to set email alerts
|

DFT calculations of the redox potentials for the nitrosyl complexes [Fe2(μ‐RS)2(NO)4] with R = alkyl

Abstract: The redox potentials of alkyl substituted Roussin's red esters in tetrahydrofuran and acetonitrile were studied using the density functional theory. The geometry and electronic structures of monoanions of Roussin's red esters [Fe2(μ‐RS)2(NO)4]− (R = Me, Et, i‐Pr, t‐Bu) together with their redox potentials in solutions have been computed using GGA (BP86,PBE, BLYP), meta‐GGA (TPSS), hybrid‐GGA (B3LYP), and meta‐hybrid GGA (BMK, B1B95) combined with 6‐311++G**//6‐31G* and tzvp basis set. The BP86 functional provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies on organic nitroxide radical species can also be found in the literature. 55,215,222,352 Density functional calculations of the reduction potentials of ironcontaining nitrosyl complexes have been recently reported by Emel'yanova et al 353,354 The standard reduction potentials (in CH 2 Cl 2 solution), proton affinities, and transition-state structures for prototypical H-atom transfer reactions were predicted for a novel class of heterobimetallic CuPd and CuPt bis(m-oxo) complexes. 355 The influence of the size of the heteroatom X on the redox potentials of hetero-polytungstates [XW 12 O 40 ] qÀ (X = B, Al, Ga, Si, Ge, P, As) in water was investigated by density functional theory using the dielectric continuum approximation.…”
Section: Applicationsmentioning
confidence: 97%
“…Studies on organic nitroxide radical species can also be found in the literature. 55,215,222,352 Density functional calculations of the reduction potentials of ironcontaining nitrosyl complexes have been recently reported by Emel'yanova et al 353,354 The standard reduction potentials (in CH 2 Cl 2 solution), proton affinities, and transition-state structures for prototypical H-atom transfer reactions were predicted for a novel class of heterobimetallic CuPd and CuPt bis(m-oxo) complexes. 355 The influence of the size of the heteroatom X on the redox potentials of hetero-polytungstates [XW 12 O 40 ] qÀ (X = B, Al, Ga, Si, Ge, P, As) in water was investigated by density functional theory using the dielectric continuum approximation.…”
Section: Applicationsmentioning
confidence: 97%
“…The cobalamin redox potentials were also calculated theoretically [56,64]. The calculations performed with BP86 functional show that it gives good results for redox potentials of transition metal complexes [36][37][38]. Generally, it can be noted (Table 5) that the BP86 calculated redox potentials are in good agreement with the experimental data (maximum difference up to 0.2 eV).…”
Section: Redox Potentialsmentioning
confidence: 63%
“…This functional allows to get a good description of the cobalt-methyl bond in alkylcobalamins, while the hybrid functionals significantly underestimate the energy of this bond [32][33][34][35]. Calculations for transition metal complexes show that BP86 functional gives also good estimation for redox potentials [36][37][38]. In the present study, BP86 is used to determine geometry, methyl binding energies and redox potentials for the investigated cobalt and nickel complexes.…”
Section: Introductionmentioning
confidence: 89%
“…All selected functionals, both local (Bp86, PW91PW91, BLYP, TPSSTPSS) and hybrid (B3LYP, B3PW91, TPSSh), describe the geometry of complex I quite satisfactorily, while for binuclear nitrosyl iron complexes [39,40], hybrid functionals usually give rise to errors in the bond lengths and the structure of the complex. As can be seen in Table 1, meta-hybrid functional TPSSh gives rise to the distances and the angles closest to the experimental ones (Dr, an average discrepancy in the bond lengths, is 0.019 Å, D°, an average discrepancy in the angles, is 3°).…”
Section: Geometry Optimizationmentioning
confidence: 98%